Lounging with robots – social spaces of residents in care: A comparison trial. (2nd December 2015) - Peri, Kathryn; Kerse, Ngaire; Broadbent, Elizabeth; Jayawardena, Chandimal; Kuo, Tony; Datta, Chandan; Stafford, Rebecca; MacDonald, Bruce
Abstract : Aims: To investigate whether robots could reduce resident sleeping and stimulate activity in the lounges of an older persons' care facility. Methods: Non‐randomised controlled trial over a 12‐week period. The intervention involved situating robots in low‐level and high‐dependency ward lounges and a comparison with similar lounges without robots. A time sampling observation method was utilised to observe resident behaviour, including sleep and activities over periods of time, to compare interactions in robot and no robot lounges. Results: The use of robots was modest; overall 13% of residents in robot lounges used the robot. Utilisation was higher in the low‐level care lounges; on average, 23% used the robot, whereas in high‐level care lounges, the television being on was the strongest predictor of sleep. Conclusion: This study found that having robots in lounges was mostly a positive experience. The amount of time residents slept during the day was significantly less in low‐level care lounges that had a robot.